Determination of Optimum Tilt Angle for Different Photovoltaic Technologies Considering Ambient Conditions: A Case Study for Burdur, Turkey - Ayaz, Ramazan; Durusu, Ali; Akca, Hakan (ASME, 2017)
This study presents a numerical approach to calculate the optimum photovoltaic (PV) tilt angle by considering the three different PV technologies (monocrystalline, polycrystalline, and thin film). This analysis focuses on determination of optimum tilt angle considering seasonal and yearly solar radiation on a plane (Wh/m(2)) and seasonal and yearly energy production (Wh) of PVs. The angle at maximum global radiation and maximum energy output is considered as the optimum tilt angle. It is found that optimum tilt angles obtained by total radiation and total energy output are different from each other considering seasonal and yearly base. Total radiation-based tilt angle results show that the optimum tilt angle is 13 deg in spring, 9 deg in summer, 17 deg in autumn, 12 deg in winter, and 12 deg as yearly. Energy production-based optimum tilt angles vary from 5 deg to 13 deg for monocrystalline, from 11 deg to 15 deg for polycrystalline, and from 12 deg to 25 deg for thin film technology according to seasonal and yearly tilt angle results.
Keywords: GLOBAL SOLAR-RADIATION; ORIENTATION; SLOPE; MODELS; PERFORMANCE; COLLECTORS; SUNSHINE; INCIDENT; PLATE; Energy & Fuels; Engineering